2012
DOI: 10.1097/spv.0b013e31824b76bd
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Affects the Glycosaminoglycan Layer of the Murine Bladder

Abstract: Objectives Urinary tract infections (UTIs), commonly caused by uropathogenic Escherichia coli (UPEC), confer significant morbidity among postmenopausal women. Glycosaminoglycans (GAGs) comprise the first line of defense at the bladder’s luminal surface. Our objective was to use a murine model of menopause to determine whether estrogen status affects the GAG layer in response to UPEC infection. Methods Adult female mice underwent sham surgery (SHAM, n = 18) or oophorectomy (OVX, n = 66) to establish a murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…We have previously shown that levels of a GAG-sulfating enzyme, HS6ST1, a key modulator of Bmp4 signaling, are increased upon infection (49). Additionally, we have shown that estrogen plays a key role in influencing the GAG thickness and the increased expression of GAG sulfation enzymes over the course of UPEC infection (29). Together, this leads us to speculate that increased sulfation of GAGs may modulate the downregulation of Bmp4 signaling and thereby the USC niche response to infection.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have previously shown that levels of a GAG-sulfating enzyme, HS6ST1, a key modulator of Bmp4 signaling, are increased upon infection (49). Additionally, we have shown that estrogen plays a key role in influencing the GAG thickness and the increased expression of GAG sulfation enzymes over the course of UPEC infection (29). Together, this leads us to speculate that increased sulfation of GAGs may modulate the downregulation of Bmp4 signaling and thereby the USC niche response to infection.…”
Section: Discussionmentioning
confidence: 81%
“…Seven-to 8-week-old C57BL/6 female mice (NCI Mouse Repository, Frederick, MD) were anesthetized and the ovaries excised as described previously (29). For sham surgery, the same procedures were performed without removal of the ovaries.…”
Section: Methodsmentioning
confidence: 99%
“…8a2, the yz cross-section image at a higher magnification shows the thickness of the fluorescent nanogel-covered layer. This thickness approximately corresponds to the GAG layer on the urothelium surface, which has been reported to the 30-50 lm in the thickness (Anand et al, 2012;Birder and Andersson, 2013). In addition, quantification of fluorescence intensity was also carried out by integrating the intensity throughout the whole volume scanned by CLSM at a fixed magnification for a fixed area of 1.62 Â 10 6 lm 2 .…”
Section: Ex Vivo Evaluation Of Mucoadhesivity Of Fitc-pam-nh 2 On Thementioning
confidence: 99%
“…Furthermore, in murine models, decreases in estrogen have been found to be related to delayed development of the protective bladder glycosaminoglycan layer, increasing susceptibility to bacterial colonization and IBC formation. 49 Postmenopausal women aged ≥ 70 years face unique challenges with regard to RUTI due to institutionalization and decreased functional status. Increased rates of catheterization, incontinence, and prolapse surgery lead to a substantial increase in risk of RUTI in this specific population.…”
Section: Risk Factorsmentioning
confidence: 99%